PESONA PEREMPUAN DALAM ILUSTRATIF STILISTIKA GEGURITAN SEWAGATI - Sutika, I Nyoman Duana (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
The study titled "The Charm of Women in the Illustrative Stylistics of Sewagati’s Geguritan" seeks to portray the visual image (charm) of women through the elegant style of the Balinese language. A woman’s beauty, from her hair and face to her movements and other physical features, is described in harmony with the universe's elements. The beauty and perfection of the universe, as reflected in the Geguritan Sewagati, appear to be embodied in the character of Ni Sewagati. Ni Sewagati is depicted as the ideal woman, whose allure is emphasized through the use of the unique Balinese language style (Balinese paribasa). The research methodology involved literature review for acquiring and presenting the data analysis results. The findings of this study contribute to enriching linguistic knowledge. This research is intended to inspire younger generations to continue appreciating and understanding traditional Balinese literature (gaguritan) on a deeper level and to serve as a reference for similar future studies.